Menelusuri Praktik Akuntansi Perbankan Dalam Kegiatan Operasional Bank: pada Bank Cimb Niaga Syariah Kota Makassar - Ambarwati Akib; Magfirah Wahyu Ramadhani; Nurul Chalisa Majiding; Sri Utami; Syahir Fadli (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to explore banking accounting practices in the daily operational activities of Bank CIMB Niaga Syariah KCP Jalan Veteran Selatan, Makassar. The approach used is qualitative descriptive with in-depth interview methods, direct observation, and documentation. The results of the study indicate that the accounting recording system for current and savings products is carried out in accordance with sharia principles through mudharabah and wadi'ah contracts, with transparent and orderly fund management. In terms of security, the bank implements a multi-layered verification system and has been certified ISO 27001 for customer data protection. Handling of problematic loans is carried out in stages, through the issuance of warning letters, mediation, to auctions as the last option, while still prioritizing a polite and cultured approach. This finding confirms that banking accounting practices at the branch level do not only focus on technical aspects, but also reflect ethical values ​​of service and customer protection).